Hedging U.S. metals & mining Industry's credit risk with industrial and precious metals - Zaghum Umar; Syed Jawad Hussain Shahzad; Dimitris Kenourgios (Resources Policy, 2019)
This study examines the conditional correlation and the resulting optimal hedge ratios between the Credit Default Swap (CDS) spreads of the U.S. metal and mining industries, and the prices of copper, platinum, silver and gold using the daily date from December 14, 2007 to August 18, 2018. It compares volatility and conditional correlation of the CDSs and the metal prices by employing multivariate GARCH family models which capture distinct characteristics of financial time series. It utilizes rolling window estimation techniques and constructs the one-step-ahead out-of-sample forecasts for the dynamic conditional correlations and thereafter the optimal hedge ratios. In general, our results show that copper provides the best possible hedge for dealing with the U.S. metals and mining industries’ credit risks. Our results are robust under alternate model specifications, choice of model refits and distributional assumptions.